1995
DOI: 10.1017/s0033822200014740
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Dating of Scrolls and Linen Fragments from the Judean Desert

Abstract: We report on new 14C measurements of samples of 18 texts (scrolls) and 2 linen fragments from Qumran Caves 1, 2, and 4 and from Nahal Hever, both in the Dead Sea region. The radiocarbon results are in good agreement with estimates of age based on paleography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…With the advent of accelerator mass spectrometry (AMS) to obtain 14 C dates in the late 1970s, it became possible to date samples cut from the margins of individual texts written on animal skin and papyrus. Two series of 14 C dates on Dead Sea Scrolls were measured at Zurich (Bonani et al 1992) and at Tucson (Jull et al 1995). These 2 series comprise 31 different Dead Sea texts, 19 of which were from caves in the vicinity of Qumran.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of accelerator mass spectrometry (AMS) to obtain 14 C dates in the late 1970s, it became possible to date samples cut from the margins of individual texts written on animal skin and papyrus. Two series of 14 C dates on Dead Sea Scrolls were measured at Zurich (Bonani et al 1992) and at Tucson (Jull et al 1995). These 2 series comprise 31 different Dead Sea texts, 19 of which were from caves in the vicinity of Qumran.…”
Section: Introductionmentioning
confidence: 99%
“…If modern castor oil is present and is not removed prior to dating, the 14 C dates will be skewed artificially towards modern values. In Rasmussen et al (2001), it was shown that the standard AAA pretreatment procedure used in the 2 previous studies dating Dead Sea Scroll samples (Bonani et al 1992;Jull et al 1995) is not capable of removing castor oil from parchment samples. In the present work, we show that it is unlikely that castor oil reacts with the amino acids of the parchment proteins, a finding which leaves open the possibility of devising a cleaning method that can effectively remove castor oil.…”
mentioning
confidence: 99%
“…All calibrated ages presented from the Tucson and Zurich studies were derived using the bidecadal Stuiver and Pearson (1986) calibration curve, except for an invocation of the decadal Stuiver and Becker (1986) curve in one instance by Jull et al (1995). In Table 1 we use ranges derived from the Stuiver et al (1998) curve (as reported by Doudna 1998) for the two Zurich and the seven Tucson documents of relevance, since these show some important differences from the Stuiver and Pearson (1986) ones.…”
Section: C Dating Of Scroll Samples Extension Of Results Using Stumentioning
confidence: 99%
“…In a footnote to their 'Atigot publication of the results Jull et al (1996) dating. The authors of the Zurich report judged that "the possibility that the leather was preserved uninscribed for such a long period is quite unlikely" (although without taking into account the Essene habits), and suggested that contamination in this specific case could not be ruled out.…”
Section: (4qppsa)mentioning
confidence: 99%
“…The approximate age was known from relative chronology (Humbert and Gunneweg, 2003;Michniewicz 2009), historical sources e.g. Josephus Flavius and Plinius the Older and previous absolute dating of different materials (Jull et al, 1996;Taylor and Higham, 1998;Van Der Plicht et al, 2003;Higham et al, 2003). The investigated carbonate binders originate from the ancient settlements Qumran, situated at the west coast of the Dead Sea.…”
Section: Sample Locationmentioning
confidence: 99%